2016
DOI: 10.1080/01634372.2016.1196284
|View full text |Cite
|
Sign up to set email alerts
|

“The Wisdom of Age”: Perspectives on Aging and Growth among Lesbian Older Adults

Abstract: Older lesbian-identified women are a health disparate yet resilient population about whom knowledge is limited and emerging. Among the areas in need of research are older lesbians' experiences of later life and stress-related growth. This article presents the findings from a qualitative study that investigated older lesbians' experiences of adversity and adaptation as they age. In-depth, exploratory interviews were conducted with 12 lesbian-identified women who were between the ages of 65-80. This study applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Additionally, respondents described a number of coping resources used as prevention or intervention approaches to acute and chronic health challenges and aging-related concerns, including engagement in regular exercise, volunteering in the community, developing a spiritual sense of self, and seeking information from legal representatives, medical personnel, and LGBTQ community groups. These results have some patterns in common with the study by Putney et al (2016) among older lesbians, despite differences in the gender and racial make-up of participants. Our study similarly identified spirituality as important for meaning-making and comfort in the face of health issues, as well as an acceptance of one’s mortality (which was treated by Putney et al as an example of development growth in late life, rather than a coping strategy).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Additionally, respondents described a number of coping resources used as prevention or intervention approaches to acute and chronic health challenges and aging-related concerns, including engagement in regular exercise, volunteering in the community, developing a spiritual sense of self, and seeking information from legal representatives, medical personnel, and LGBTQ community groups. These results have some patterns in common with the study by Putney et al (2016) among older lesbians, despite differences in the gender and racial make-up of participants. Our study similarly identified spirituality as important for meaning-making and comfort in the face of health issues, as well as an acceptance of one’s mortality (which was treated by Putney et al as an example of development growth in late life, rather than a coping strategy).…”
Section: Discussionsupporting
confidence: 73%
“…The narratives related to coping with health challenges did not as clearly emphasize the role of social support, building connections with other LGB people, resisting cultural norms, or dealing with feelings about one’s sexual orientation, which previous research has suggested may be important (Fredriksen-Goldsen et al, 2015; Putney et al, 2016; Van Wagenen et al, 2013). While there were certainly some narrative threads around these topics among a few participants, including the importance of spiritually coming to terms with sexual orientation (Tony) and some examples of resisting heterosexist, racist and ageist norms, these topics were not strong narratives across the sample in connection to coping with health problems.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Normalization of LGBT culture may benefit younger men who are less incentivized to seek mentorship and social contact with older gay men. Putney et al, 2016 Emotional: Narratives from interview transcripts reflected a growing sense of belonging later in life.…”
Section: Structurementioning
confidence: 99%
“…Models of resilience include conceptual frameworks such as stress-related growth (SRG) and posttraumatic growth (PTG). Bonet, Wells and Parsons [ 60 ] explored SRG as an aspect of the coming out process for lesbian and bisexual women, Putney, Leefmeaker and Herbert [ 61 ] have looked at aging lesbians, SRG and social support, while Golub, Walker et al [ 62 ] explored SRG, social support and HIV risk for transgender women and Calabrese et al [ 63 ] looked at SRG for SMW in terms of minority stress. Although stress-related growth touches on some of the same factors of personal improvement following stress, there are critical epistemological differences in that SRG encompasses developmental life stressors and everyday stressors, whereas PTG focuses on a traumatic event in which someone’s assumptive world is challenged and shattered [ 53 , 64 ].…”
Section: Posttraumatic Growthmentioning
confidence: 99%